Online Experiments and Participation Within Chile S Extraordinary Constitutional Process - Baigorrotegui-Baigorrotegui, G (Association for Computing Machinery, 2021)
We write this article coming from a troubled and uncertain situation. The Chilean democracy has not been sensitive or responsive to the people’s demands for greater equality and dignity. The so-called Penguin Revolution in 2006, the student mobilizations of 2011, the feminist protests of May 2018, and the demonstrations for No+AFP in 2017 are just some of the acts of civil disobedience and resistance that Chile has experienced during the past two decades.